Infectious bursal disease vaccine delivery via topical application in 18-day-old specific pathogen free embryonated chicken eggs - W., Mukminah Sakinah (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2013)
The purpose of this study was to investigate the effect of vaccination against infectious bursal disease (IBD) via topical application of IBD vaccine (MyVAC UPM93) either with or without liposomes as vaccine carrier in 18-day-old specific pathogen free (SPF) embryonated chicken eggs. The study demonstrated that the IBD vaccine group alone could induce high and protective level of IBD antibody titre (2545+1884 ELISA unit) in the chicks at 14 days of age. In contrast, IBD antibody titre was not detected in the liposomes, combination of liposomes with IBD vaccine and control groups of chickens. It appears that further study is needed to improve the liposome as a vaccine carrier to accelerate vaccine delivery to the target organ and enhance antibody titre. It was concluded that topical application of IBD vaccine (MyVAC UPM93) in 18-day-old SPF embryonated chicken eggs can be an effective vaccination route against IBD.